Biomonitoramento e citogenética dos afluentes do rio Paranaíba - Silva, Sabrina Vaz dos Santos e (2013)
CHAPTER II: Rhamdia quelen, commonly known as catfish, has a broad distribution from south Mexico to Argentina. R. quelem has an important role in Brazilian aquaculture, been one of the most farmed species, mainly because of the great acceptance of the consumer market. This present study focused to analyze the frequency of B chromosomes and characterize nucleolus organizer region (NOR) in five populations of Rhamdia quelen from Triângulo Mineiro, Brazil. In cytogenetic analysis, B chromosomes were found in both genders. The populations from Bebedouro, Pedras and Tejuco river presented 0-2 B chromosomes; the specimens from Araguari river 0-4 B chromosomes; however, in Uberabinha river, all metaphase analyzed had B chromosome, with variation of 1-3. The Uberabinha population showed multiple Ag-NORs in the long arms of the sub metacentric chromosomes, whilst in Tijuco s population, the NOR is located on the interstitial region of the sub metacentric pair. The C band pattern showed small heterochromatic blocks in the centromeric and telomeric regions in Uberabinha. Our data demonstrate new crucial results that suggest taxonomic revision. CHAPTER III: The rivers from the micro region of Catalão, Goiás State, Brazil are exposed to intense anthropogenic influences, such as agricultural activities, industry and urban waste. The genotoxicity of three points of the micro region were analyzed with the Micronucleus test. Accordingly to the results of the study, the species in sites 1, 2 and 3 exhibited an increase in their frequency of MN compared to specimens from site 4 (p>0.01). Significant increases in the frequency of micronuclei (MN) occurred in erythrocytes of A. fasciatus and A. altiparanae at sites 1 and 2. At site 3 is possible to observe higher frequencies of MN in C. fasciatum. The MN induction in C. fasciatum was correlated to chromium in water and sediment, whilst A. fasciatum and A. altiparanae showed small correlation with zinc in water and sediment. This data suggest that benthic and nektonic species have different sensitivities in relation to heavy metal ions.